Medical training to effectively support patients who use substances across practice settings: a scoping review of recommended competencies - Ausman, Christine; Almatar, Dawoud; Kiepek, Niki (Canadian Medical Education Journal, 2024)
Background: The responsibility for addressing the healthcare needs of PWUS is the responsibility of all physicians. Within the healthcare system, research consistently reveals inequitable experiences in healthcare with people who use substances (PWUS) reporting stigmatization, marginalization, and a lack of compassion. Objectives: The aim of this scoping review was to find and describe competencies being taught, developed, and fostered within medical education and then to provide recommendations to improve care for this population of patients. Results: Nineteen articles were included. Recommended knowledge competencies tend to promote understanding neurophysiological changes caused by substances, alongside knowing how to evaluate of ‘risky’ behaviours. Commonly recommended skills relate to the screening and management of substance use disorders. Recommended attitude competencies include identifying personal bias and establishing a patient-centered culture among practice teams. The disease model of addiction informed all papers, with no acknowledgement of potential beneficial or non-problematic experiences of substance use. To enhance knowledge-type competencies, medical education programs are advised to include addiction specialists as educators and prevent stigmatization through the hidden curriculum. Conclusion: To reduce experiences of stigmatization and marginalization among patients who use illicit substances and to improve quality of care, knowledge, skills, and attitudes competencies can be more effectively taught in medical education programs.